Pollution haven hypothesis (PHH) - Burcu Ozcan (Elgar Encyclopedia of Energy Economics, 2025)
OBJECTIVES: To describe trends in state-level abortion policies before the Dobbs v Jackson Supreme Court decision, distinguishing laws that have been enacted through legislation/regulation and are thus "on-the-books" from laws that are enforceable, ie, "on-the-books" laws not blocked by court decisions or attorney general opinions. DESIGN: We used policy surveillance methods to build a database of enforceable and "on-the-books" state-level abortion policies from January 1, 2005, to June 1, 2022. We describe trends over time in enforceable policies and assess differences in enforceable and "on-the-books" policies within state-years. SETTING: United States. PARTICIPANTS: States in the United States. MAIN OUTCOME MEASURES: Abortion policies enforceable or "on-the-books" at the state-level. RESULTS: There were multiple changes in enforceable policies within states over time, with the greatest number in requirements regarding private insurance coverage of abortion (28 states) and the fewest in Medicaid coverage of abortion (3 states). Changes were concentrated in the same subset of states (eg, 6 states had changes in 7 policies while 9 had changes in zero policies). We found more pronounced differences between enforceable and "on-the-books" policies for bans on abortion after specified gestations (30%), parental involvement requirements for minors (12%), abortion provider qualification requirements (9%), and mandatory waiting period requirements (8%) versus differences for hospital transfer agreement requirements (1%). CONCLUSIONS: Because of notable distinctions between enforceable and "on-the-books" abortion policies, researchers should be intentional and transparent about whether their policy exposure measures capture enforceable or "on-the-books" policies.